Discrimination and Civic Engagement of Immigrants in Western Societies.~A Systematic Scoping Review - Stephanie Müssig; Inken Okrug (Journal of International Migration and Integration, 2024)
Research has highlighted the barriers that immigrants face due to discrimination in their everyday lives. At the same time, it has been shown that immigrants get civically engaged to counteract discrimination and to work for structural change. To contribute to ongoing research on how discrimination affects attitudes, behaviour, and eventually life opportunities of immigrants, we investigate in a scoping review conceptualisations and measurements of discrimination and civic engagement used in empirical quantitative studies. We take systematic stock of publications that examine the link between discrimination—perceived and experienced—and the civic engagement of immigrants in Western societies. Using three of the leading databases for the social sciences, we systematically search for literature on discrimination and civic engagement over the past 50 years. On the basis of the retrieved publications, we assess how studies conceptualise and measure discrimination and civic engagement and investigate how scholars represent the link between discrimination and civic engagement in their statistical models. We introduce an analytical framework for discrimination that leads to more analytical clarity and may serve as a tool to investigate the link between discrimination and civic engagement more precisely. From our review, we derive recommendations as to how studies from different disciplines can learn and benefit from each other in order to gather knowledge on the mechanisms that underlie the link between discrimination and civic engagement.
Keywords: 300; Discrimination; Civic engagement; Participation; Immigrants; Muslim